2005
DOI: 10.1017/s0021859605005630
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of near infrared reflectance spectroscopy for the prediction of organic carbon concentrations in grassland soils

Abstract: SU MMARYFor the determination of soil organic carbon (OC) concentrations, the availability of a fast, low-cost analysis method is required. The aim of the present study was to evaluate the possibilities of near infrared reflectance spectroscopy (NIRS) to build a spectral database and to develop calibrations for the prediction of organic carbon concentrations in grassland soils. NIRS spectra of 1626 soil samples from different grasslands (both agricultural and natural) were collected between 1100 and 2500 nm. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…This strategy allowed, depending on the multivariate calibration type, spectral range and attribute used to split the dataset, to improve considerably the accuracy of the models. The same kind of results was obtained by Van Waes et al (2005) under laboratory conditions. They showed that dividing samples into groups according to agricultural practices or texture improved the prediction of soil organic carbon in grassland soils by 7-16%.…”
Section: Model Calibration and Validationsupporting
confidence: 77%
“…This strategy allowed, depending on the multivariate calibration type, spectral range and attribute used to split the dataset, to improve considerably the accuracy of the models. The same kind of results was obtained by Van Waes et al (2005) under laboratory conditions. They showed that dividing samples into groups according to agricultural practices or texture improved the prediction of soil organic carbon in grassland soils by 7-16%.…”
Section: Model Calibration and Validationsupporting
confidence: 77%
“…Typically soil reflectance decreases with increasing SOC in the wavelength range 0.4-2.5 μm (Baumgardner et al, 1985) and different modelling techniques are used to predict SOC from continuous reflectance spectra or derivatives Banin, 1994, 1995;Reeves et al, 2002;Udelhoven et al, 2003;van Waes et al, 2005;Brown et al, 2006;Viscarra Rossel et al, 2006). The transfer of prediction models to airborne or satellite remote sensing data has only rarely been conducted (Hill and Schütt, 2000;Gomez et al, 2008;Jarmer et al, 2010), although the approach has promise to obtain area-wide estimates of SOC distribution and support regional carbon inventories.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral derivative analysis can be used to determine the position and magnitude of absorption bands within a spectrum (Mather, 2004). Derivative analysis has been previously applied to several soil biological-physical-chemical properties estimations (Kariuki et al, 2004;Brown et al, 2005;Van Waes et al, 2005;Mutuo et al, 2006). A future and promising research area in soil radiometry is the robust identification of absorption coefficients for specific soil biogeochemical components needed for the development of soil radiative transfer models (Ustin et al, 2005), and derivative analysis is highly suitable to help in the identification of such absorption features.…”
Section: Introductionmentioning
confidence: 99%